Exploring Women’s Experiences of Online Learning Using Photography and an Online Focus Group - Jennifer H. Kelland (Adult Education Research Conference, 2007)
In this roundtable, I consider methodological questions about integrating photo-assisted interviews and an online focus group to examine women’s experiences of learning online.